Age and hatch-date distribution of Athermomorous regina (Seale, 1910) (Atherindae) in Conception, Iloilo. - Odtujan, Wenna Grace (2016.)
Age forms the basis to determine mortality rate, growth rate and other population parameters which influence life history and control the productivity of fish populations. To provide insights and information of early life traits of Atherinomorous regina, otoliths of individuals captured on December 5, 2011 and January 4, 2012 in Concepcion, Iloilo were examinded. Age was estimated from the age estimates. Increment width were used to reconstruct mean growth trajectories of individuals hatched per month. Hatch dates provide insight into the relationship between spawning behaviour and survival, revealing what environmental conditions led to enhanced survival. Growth trajectories between individuals of different hatch months allow us to compare batches that are faster growing vs. slower growing. Results show a spawning peak in July with progeny abundance likely due to reproductive activity and sexual maturation during the summer months. Mean growth rate estimated was 0.12mm/day. Faster growth of individuals spawned during July-August was observed and slower growth for rest of the individuals, suggesting a strong dependence of larval growth on spawning period, highlighting the importance of environmental conditions during spawning period on recruitment and survival.
Special Problem -- Bachelor of Science in Biology. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Athermomorous regina -- Hatch-date.